Perceived Social Support in Transgender People: A Comparative Study with Cisgender People - Vázquez, Nuria (2020)
Background: Trans people may find themselves in a situation of social discrimination, reflected in their health and in the lack of scientific research. The minority stress theory points out the importance of social support for the stress of sexual or gender minorities. This study aims to explore social support and its dimensions in this population. Method: 81 people participate, of which 36 are trans and 45 non-trans (cisgender), as a control group. The Mos Social Support Survey is applied to measure perceived social support and a questionnaire with sociodemographic variables. Results: The results show that there are no differences in the perceived social support between both groups. However, sociodemographic variables such as having a partner, age, and employment situation show change for the trans population in some dimensions. Conclusion: These findings promote future lines of research that expand the knowledge of these variables in this group.